Unveiling The Garden Of Love: A Comparative Study Of Mystical Symbolism In Layla Majnun And Gitagovinda - Sinha, Lalita (2004)

(untitled)
In this comparative study of two masterpieces of literary expression, attention is directed at unveiling similarities and differences of mystical significance between Nizami's The Story of Layla Majnzm and Love Song of the Dark Lord. Jeyadem's Gitagovinda. The study is conducted on theoretical constructs of Hermeneutics. guided by traditional norms and conventions of Persian and Sanskrit literary expression. and informed by the Traditionalist perspective of religion. These considerations represent the platform for the understanding and interpretation of elements or phenomena in the texts as symbolic expressions of the Sufi and Bhakti mystico-religious traditions.